Simultaneous PET/MR head–neck cancer imaging: Preliminary clinical experience and multiparametric evaluation. Issue 7 (July 2015) - Covello, M.; Cavaliere, C.; Aiello, M.; Cianelli, M.S.; Mesolella, M.; Iorio, B.; Rossi, A.; Nicolai, E.
Highlights: Simultaneous PET/MRI is a suitable tool for head/neck T-staging. No significant differences have been found for PET measures get by both PET/CT and PET/MRI. SUV 2D and 3D measures in HN lesion offer comparable estimations. Multiparametric evaluation allows a complete characterization of HN lesions. Abstract: Purpose: To evaluate the role of simultaneous hybrid PET/MR imaging and to correlate metabolic PET data with morpho-functional parameters derived by MRI in patients with head–neck cancer. Methods: Forty-four patients, with histologically confirmed head and neck malignancy (22 primary tumors and 22 follow-up) were studied. Patients initially received a clinical exam and endoscopy with direct biopsy. Next patients underwent whole body PET/CT followed by PET/MR of the head/neck region. PET and MRI studies were separately evaluated by two blinded groups (both included one radiologist and one nuclear physician) in order to define the presence or absence of lesions/recurrences. Regions of interest (ROIs) analysis was conducted on the primary lesion at the level of maximum size on metabolic (SUV and MTV), diffusion (ADC) and perfusion ( K trans, V e, k ep and iAUC) parameters. Results: PET/MR examinations were successfully performed on all 44 patients. Agreement between the two blinded groups was found in anatomic allocation of lesions by PET/MR (Primary tumors: Cohen's kappa 0.93; Follow-up: Cohen's kappa 0.89). There was a significant correlation between CT-SUV measures and MR (e.g., CT-SUV VOI vs. MR-SUV VOI: ρ = 0.97, p < 0.001 for the entire sample). There was also significant positive correlations between the ROI area, SUV measures, and the metabolic parameters (SUV and MTV) obtained during both PET/CT and PET/MR. A significant negative correlation was observed between ADC and K trans values in the primary tumors. In addition, a significant negative correlation existed between MR SUV and ADC in recurrent tumors. Conclusion: Our study demonstrates the feasibility of PET/MR imaging for primary tumors and recurrent tumors evaluations of head/neck malignant lesions. When assessing HNC, PET/MR allows simultaneous collection of multiparametric metabolic and functional data. This technique therefore allows for a more complete characterization of malignant lesions.